The prevalence of Helicobacter pylori infection in patients with gastric and duodenal ulcers – a 10-year, single-centre experience - Serin, Ayfer; Tankurt, Ethem; Şarkış, Cihat; Simsek, Ilkay (Gastroenterology Review/Przegląd Gastroenterologiczny, 2015)
Introduction : Helicobacter pylori ( H. pylori ) occurs throughout the world and causes gastroduodenal diseases. There is data indicating a change in the prevalence of H. pylori infection worldwide. The prevalence of H. pylori is 80% in Turkey, while it is higher in many developing countries, and the rate of infection varies throughout the world. In many developing countries, the prevalence of infection exceeds 90% by adulthood. Aim : To determine the change in the rate of H. pylori infection in gastric ulcers and duodenal ulcers for a 10-year period in a single centre. Material and methods : The study population included 550 patients (342 in 2004, 208 in 1994) with gastric and duodenal ulcers. Results : In 2004 there were 125 (36.5%) patients with gastric ulcer and 217 patients with duodenal ulcer (64.5%). CLO test positivity was 39.2% in patients with gastric ulcers and 60% in patients with duodenal ulcers. In 1994 there were 208 patients (159 duodenal ulcers, 49 gastric ulcers). Urease test was positive in 74.2% of patients with duodenal ulcer and in 65.2% of patients with gastric ulcer. The decrease in the rate of urease positivity in patients with gastric ulcer was statistically significant (p = 0.01) during this 10-year period. Conclusions : In the present study we found that the urease positivity decreased significantly in patients with gastric ulcer between 1994 and 2004.